2021
DOI: 10.1088/1755-1315/682/1/012070
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Doping Concentration on the Zinc Doped Nickel Oxide Nanostructures: Morphological, Structural, and Optical Properties

Abstract: The zinc doped nickel oxide (Zn:NiO) nanostructures with 0 at.% (UD), 1 at.% (1ZNO), and 2 at.% (2ZNO) of Zn concentrations were successfully deposited on the NiO seed-coated glass substrates. The films were successfully produced from two synthesis techniques: the sol-gel spin coating for NiO seed-coated and the solution immersion for the Zn:NiO nanostructures. The films were then pre-baked at 150 °C and subsequently annealed at 500 °C. The Zn doping concentrations affecting NiO in terms of morphological, stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…Along the three principal planes of (111), (200), and (220), the crystallite sizes are 37, 36, and 28 nm in NiO, and they reduce to 3.6, 4.9, and 3.6 nm in Zn:NiO, respectively. A similar decrease in crystallite size has been observed in an earlier report for Zn-doped NiO . Yet another study showed a crystallite size decrease from ∼22 to ∼20 nm on going from NiO- to Zn-doped NiO .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Along the three principal planes of (111), (200), and (220), the crystallite sizes are 37, 36, and 28 nm in NiO, and they reduce to 3.6, 4.9, and 3.6 nm in Zn:NiO, respectively. A similar decrease in crystallite size has been observed in an earlier report for Zn-doped NiO . Yet another study showed a crystallite size decrease from ∼22 to ∼20 nm on going from NiO- to Zn-doped NiO .…”
Section: Resultssupporting
confidence: 87%
“…A similar decrease in crystallite size has been observed in an earlier report for Zn-doped NiO. 28 Yet another study showed a crystallite size decrease from ∼22 to ∼20 nm on going from NiO-to Zn-doped NiO. 29 The slight mismatch in the ionic radii of Zn 2+ and Ni 2+ ions, 74 and 70 pm, induces some structural distortion, large enough to induce morphological and structural changes, but small enough to prevent structural collapse.…”
Section: Xrd and Raman Studies Onsupporting
confidence: 74%
See 1 more Smart Citation
“…Properties of zinc oxide can be enhanced by doping with other transition metal oxides. This is due to the development of new crystallographic phases in the composite [14][15][16]. Doping can be done with nickel oxide, copper oxide, titanium dioxide etc.…”
Section: Introductionmentioning
confidence: 99%